Visual function and quality of life in patients with Stevens-Johnson syndrome who received acute protocol-based ocular care - Shanbhag, Swapna S.; Tahboub, Mohammad A.; Chodosh, James; Saeed, Hajirah N. (Frontiers in Toxicology, 2022)
Purpose: To report visual function and quality of life (VF/QOL) using the National Eye Institute Visual Function Questionnaire (NEI-VFQ-25) and the ocular surface disease index (OSDI) in patients in the chronic phase of Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN). Methods: The NEI-VFQ-25 questionnaire was administered to 15 patients who received protocol-based care in the form of topical medications with or without amniotic membrane transplantation (AMT) for acute SJS/TEN. The scores obtained were compared with scores from a healthy population. The associations between the NEI-VFQ-25 and dry eye symptoms as measured by OSDI questionnaire were also studied. Results: Patients were surveyed at a mean of 4.47 ± 2.22 years after acute SJS/TEN. Eleven patients received AMT in the acute phase. The median best corrected visual acuity at the time of administration of the questionnaire was 20/20. The mean composite NEI-VFQ-25 score was 86.48 ± 12. Patients who received protocol-based treatment in the acute phase of SJS/TEN had comparable NEI-VFQ-25 scores with healthy subjects on all subscales except ocular pain (p=0.027) and mental health (p=0.014), which were significantly reduced. The NEI-VFQ-25 composite scores significantly correlated with OSDI (R = -0.75, p=0.001). Conclusions: A protocol-based management strategy composed of early ophthalmic evaluation, grading based on severity, the use of topical corticosteroids and AMT in the acute phase of SJS/TEN in patients with ocular complications helped preserve the VF/QOL. This study highlights the impact of appropriate management of the ocular complications in the acute phase of SJS/TEN.